2018
DOI: 10.1111/idh.12333
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based education: Experiences of undergraduate dental therapy students at the University of KwaZulu‐Natal, South Africa

Abstract: The reported experiences of undergraduate dental therapy students involved in community-based clinical training suggest that students gained awareness of the context-specific challenges facing communities and health professionals in different oral health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Increasing students’ awareness through community participation about social and financial determinants of poor oral health may aid them to appreciate the value of their professional contributions in providing care for underserved and medically indigent population. [2122] In our study, it is interesting to note that majority of the dental students responded that they tried to assess patients’ socioeconomic status before treatment. Students felt that assessing the socioeconomic status may guide to plan treatment accordingly.…”
Section: Discussionmentioning
confidence: 96%
“…Increasing students’ awareness through community participation about social and financial determinants of poor oral health may aid them to appreciate the value of their professional contributions in providing care for underserved and medically indigent population. [2122] In our study, it is interesting to note that majority of the dental students responded that they tried to assess patients’ socioeconomic status before treatment. Students felt that assessing the socioeconomic status may guide to plan treatment accordingly.…”
Section: Discussionmentioning
confidence: 96%
“…40,58,73 17,45,[74][75][76][77][78][79][80] social accountability, 39 a patient-centred and holistic care approach, [18][19][20]25,29,31,34,35,38,56,[64][65][66]68,72,[81][82][83][84][85][86][87][88][89][90] civic/ community engagement, 42,47,75,78 professionalism, 17,32,68,80,91 ethical skills/responsibility 19,20,22,32,35,…”
Section: Motivations and Intentions Of Community Education Programmementioning
confidence: 99%
“…Three papers published prior to 2002 (n = 3/8, 37.5%) demonstrated that community education programmes peaked in the 1970s and were funded by government grants; the grants were used to incentivise dental schools to develop rotations for their students outside the university in order to broaden dental students' education and serve the community. 40,58,73 17,45,[74][75][76][77][78][79][80] social accountability, 39 a patient-centred and holistic care approach, [18][19][20]25,29,31,34,35,38,56,[64][65][66]68,72,[81][82][83][84][85][86][87][88][89][90] civic/ community engagement, 42,47,75,78 professionalism, 17,32,68,80,91 ethical skills/responsibility…”
Section: Motivations and Intentions Of Community Education Programmementioning
confidence: 99%
See 2 more Smart Citations